ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KLAIM DAN STRATEGI PENYELESAIANNYA DALAM INDUSTRI KONSTRUKSI - MOHAMMAD MUHLIS; MOCHAMAD VALDIANSYAH (JURNAL DAKTILITAS, 2023)
Abstrac The economic development of a country is greatly influenced by the building industry. The emergence of problems in this sector must be minimized. The problem of claims is one of them. Parties involved in this industry must have knowledge of the different types of claims, their causes, and the solutions that can be made to overcome claim problems. Types and reasons for claims include (a) claims for losses due to contract modifications made by the owner, (b) claims for additional contract value components, (c) claims due to changes in activities, and (d) claims due to project suspension. Some examples of anticipatory measures are document preparation and understanding of the contract, briefing on reserving rights, planning and scheduling, proactive measures, and change orders. In addition, there are other means of reaching settlement, including negotiation, mediation, arbitration, and litigation. Keywords: Building sector, Claims Abstrak Perkembangan ekonomi suatu negara sangat dipengaruhi oleh industri bangunan. Timbulnya masalah di sektor ini harus ditekan seminimal mungkin. Masalah klaim adalah salah satunya. Pihak-pihak yang terlibat dalam industri ini harus memiliki pengetahuan tentang berbagai jenis klaim, penyebabnya, dan langkah-langkah yang dapat diambil untuk menyelesaikan masalah klaim. Jenis dan alasan klaim meliputi (a) klaim atas kerugian akibat modifikasi klaim pemilik, klaim untuk komponen nilai kontrak tambahan, klaim akibat perubahan kegiatan, dan klaim akibat penangguhan proyek adalah contoh-contoh klaim. Beberapa contoh akta antisipatif adalah persiapan dokumen dan pemahaman kontrak, penjelasan ringkas tentang pemesanan hak, perencanaan dan penjadwalan, tindakan proaktif, dan perintah perubahan. Selain itu, terdapat cara lain untuk mencapai penyelesaian, termasuk negosiasi, mediasi, arbitrase, dan litigasi. Kata kunci ; Sektor bangunan, Klaim